Analisis Distribusi Tenaga Kesehatan di Indonesia Menggunakan K-Means Clustering - Pahlevi, Muhammad Adjie; Abimanyu, Anggito; Arrizqy, Muhammad Hafizh; Ryaldi, Achmad (JATISI, 2024)
The distribution of health workers that is equitable and in accordance with the needs of each region is a crucial factor in improving the quality of health services. This study aims to analyze the distribution of health workers in Indonesia through the K-Means Clustering method. The data used is data on the number of health workers by province in 2023 reported by the Central Statistics Agency (BPS). The analysis results prove that health workers in Indonesia are divided into several clusters with different characteristics. Through the identification of this distribution pattern, this study is expected to provide useful insights to policy makers in determining priorities and strategies for more effective and efficient allocation of health workers. The results also provide a basis for policy development that is more responsive to the real needs in the field, so as to support the achievement of better equitable health services throughout Indonesia.